Subjective social well-being of employees with different socioeconomic statuses - Blynova, Olena Yevhenivna; Kruhlov, Kostiantyn Oleksandrovych (Insight: the psychological dimensions of society, 2021)
The purpose of the research is to specify differencesin the subjective social well-being of an organization’semployees with different socioeconomic statuses.The following methods have been used to conductthe empirical research (n = 38): theoretical analysisand generalization of scholarly views of the problem;empirical methods: “Questionnaire of SubjectiveSocial Well-Being” (T.V. Danylchenko); “Questionnaireof Subjective Economic Well-Being” (V.O. Khashchenko);the methods of statistical analysis: correlation analysis;F-test. Results. The authors have established statisticallysignificant correlations between the criteriaof subjective social well-being and subjective economic well-being, namely, between the scales “Social visibility”,“Social remoteness” and the indices of economicoptimism, economic anxiety, and financial deprivation.It has been confirmed the statistical interdependencebetween the scales “Emotional acceptance” and “Familywell-being index”. The research has determined differencesbetween employees’ groups, which were dividedaccording to socioeconomic status (managers and “performers”),on the following scales: “Social visibility”,“Positive social perceptions”, and “Economic optimismindex”. Conclusions. The employees with higher socioeconomicstatus recognize their influence, the capabilityto settle problems, the availability of social ties,financial, economic, material, and social resources dueto which they are confident when coping with stressfulsituations, have a positive economic expectation, a highlevel of efficient social functioning. The employees withlow socioeconomic status are mainly characterized byunsatisfactory emotional and social relations, a failureto actively influence their social environment; they feeleconomic anxiety about their finances and the future.